A two-photon fluorescent probe for real-time monitoring of autophagy by ultrasensitive detection of the change in lysosomal polarity. Issue 26 (28th February 2017) - Jiang, Jiacheng; Tian, Xiaohe; Xu, Changzhi; Wang, Shuxin; Feng, Yan; Chen, Man; Yu, Haizhu; Zhu, Manzhou; Meng, Xiangming
Abstract : The first two-photon probe, Lyso-OC, was proposed for use in monitoring cell autophagy by detection of the change in the lysosomal polarity during the membrane fusion process. Abstract : The first two-photon probe, Lyso-OC, was proposed for use in monitoring cell autophagy by detection of the change in the lysosomal polarity during the membrane fusion process of autophagy. TheLyso-OC probe exhibited desirable optical properties and a detection signal that was selective to the polarity change. More importantly, Lyso-OC displayed real-time monitoring of autophagy in living cells.